AS CONSEQUÊNCIAS DE ESQUECER AUSTIN : (CONCEPÇÕES DE CONTEXTO E VARIEDADES DE CONTEXTUALISMO) - Miguens, Sofia (Prometheus - Journal of Philosophy., 2020)
J.L. Austin claimed: “When we examine what we should say when, what words we should use in what situations, we are looking again not merely at words (or “meanings”, whatever they may be) but also at the realities we use words to talk about”. In this article I will examine the way Michael Williams (Williams, 2018, 2019) follows Austin’s lead in recent exchanges with another epistemologist, Duncan Pritchard (Pritchard, 2016), in order to spell out some (bad) consequences of forgetting Austin when one is a contextualist. One main goal of the article is to identify different conceptions of context underlying varieties of epistemic contextualism.